How Much Law Does the School System Need? - Miro Cerar (Central European Public Administration Review)
In its ideal form, the law is a guardian of the freedom and autonomy of the school system. On the other hand, the school system must, as part of its responsibility, establish a respectful and responsible attitude toward the rule of law. In Slovenia, practice deviates from such ideal to too great an extent. Excessive and inappropriate legal regulation reduces the freedom and autonomy of the school system. The consequences within this system are: partly ignored legal regulations, and the resulting ineffectiveness; excessive legal administration in schools; increased teachers’ opposition to the law; a lack of teachers’ motivation; and, as a consequence, worsened quality of the educational process. The law, however, is only a part of the problem. The latter has its roots mainly in a general disorientation of society with regard to its values. In order to establish the right measure and manner of the legal regulation of the school system, the moral and common sense basis of society must first be healed and strengthened.